Effect of seven newly synthesized and currently available oxime cholinesterase reactivators on cyclosarin-intoxicated rats - Karasova, Jana Zdarova; Kassa, Jiri; Musilek, Kamil; Pohanka, Miroslav; Novotny, Ladislav; Kuca, Kamil (International journal of molecular sciences, 2009)
Seven new oxime-based acetylcholinesterase reactivators were compared with three currently available ones (obidoxime, trimedoxime, HI-6) for their ability to lessen cholinesterase inhibition in blood and brain of cyclosarin-treated rats. Oximes were given at doses of 5% their LD(50) along with 21 mg/kg atropine five min before the LD(50) of cyclosarin (120 ug/kg) was administered. Blood and brain samples were collected 30 minutes later. The greatest difference between acetylcholinesterase inhibition in blood of cyclosarin-treated rats was found after administration of HI-6 (40%), compared to 22% for trimedoxime and 6% for obidoxime. Only two of the seven newly synthesized oximes had any effect (K203 at 7%, K156 at 5%). Effective oximes against cyclosarin-inhibited plasma butyrylcholinesterase were HI-6 (42%), trimedoxime (11%), and K156 (4%). The oximes were less effective in brain than in blood, with reactivation values for HI-6 30% against acetylcholinesterase and 10% against butyrylcholinesterase. Values for newly synthesized oximes were less than 10% for K206, K269 and K203.
Keywords: Animals; Acetylcholinesterase; vztah mezi dávkou a účinkem léčiva; Rats, Wistar; Atropine; oximes; Organophosphorus Compounds; oximy; cyclosarin; acetylcholinesterase; organofosforové sloučeniny; mozek; reactivators; Dose-Response Relationship, Drug; Oximes; Male; acetylcholinesterasa; Brain; reaktivátory cholinesterasy; krysa rodu Rattus; butyrylcholinesterase; zvířata; mužské pohlaví; atropin; Rats; Cholinesterase Reactivators; potkani Wistar